2005
DOI: 10.1161/01.cir.0000155620.10387.43
|View full text |Cite
|
Sign up to set email alerts
|

Resistin Is an Inflammatory Marker of Atherosclerosis in Humans

Abstract: Background-Resistin, a plasma protein, induces insulin resistance in rodents. Recent reports suggest that circulating levels of resistin are elevated in obese and insulin-resistant rodents and humans. Whereas rodent resistin is made in adipocytes, macrophages are a major source of human resistin. Given the convergence of adipocyte and macrophage function, resistin may provide unique insight into links between obesity, inflammation, and atherosclerosis in humans. Methods and Results-We examined whether plasma r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
624
16
22

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 796 publications
(709 citation statements)
references
References 58 publications
(71 reference statements)
47
624
16
22
Order By: Relevance
“…A growing amount of data support the interrelationship of eGFR with inflammatory involvement as well as a distinct role of low-grade inflammation in the progression of chronic kidney disease 3,9,14,15 and diffuse atherosclerosis reflected by microalbuminuria. 25,26 In these lines, although resistin mediates diverse biological effects of cytokines, [27][28][29] there was a lack of association between resistin and white blood cell count in our population, a finding that is in contrast with previous reports. 6,28 It should be noted that other more sensitive markers of subclinical inflammation such as C-reactive protein were not estimated in this study, thus the link between hyperresistinemia and inflammation may be missed.…”
Section: Discussioncontrasting
confidence: 99%
“…A growing amount of data support the interrelationship of eGFR with inflammatory involvement as well as a distinct role of low-grade inflammation in the progression of chronic kidney disease 3,9,14,15 and diffuse atherosclerosis reflected by microalbuminuria. 25,26 In these lines, although resistin mediates diverse biological effects of cytokines, [27][28][29] there was a lack of association between resistin and white blood cell count in our population, a finding that is in contrast with previous reports. 6,28 It should be noted that other more sensitive markers of subclinical inflammation such as C-reactive protein were not estimated in this study, thus the link between hyperresistinemia and inflammation may be missed.…”
Section: Discussioncontrasting
confidence: 99%
“…38 Available data also support a role of r in determining an increase of inflammation and atherosclerosis. 39 The positive effect of losartan in reducing r had already been observed in an experimental model of acute hyperinsulinemia in healthy humans. 40 However, to the best of our knowledge, no other study, except ours, has evaluated the effects of either losartan or ramipril on such a large spectrum of adipokines.…”
Section: Correlationsmentioning
confidence: 88%
“…We tested whether in the athletes an increased serum resistin concentration reflected ongoing pro-inflammatory events. In fact, resistin's structure is similar to that of proteins involved in inflammatory processes and its serum concentration was found to be associated with coronary artery calcification independently of the C-reactive protein and other inflammatory markers [17]. In addition, exercise activity is known to induce acutely increments of the circulating levels of many pro-and anti-inflammatory cytokines and chemokines [31].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies in humans reported conflicting results, indicating decreased or increased resistin levels in obesity, opposite responses to insulin-sensitisers and contradictory correlations between resistin and markers of insulin resistance [8][9][10][11][12][13][14][15]. It has also been suggested that resistin plays a role in inflammatory conditions, because it is expressed in human macrophages [16] and because recent data have supported the existence of an independent association of resistin with the inflammatory factors IL-6 and C-reactive protein [17]. The aim of the present study was to examine whether resistin is a marker of insulin resistance or lowgrade inflammation in a human model of extreme insulin sensitivity, i.e.…”
Section: Introductionmentioning
confidence: 99%